Concurrent Hand and Penile Gangrene following Prolonged Warfarin Use; a Case Report - Mahdizadeh, Fatemeh; Safari, Saeed (Archives of Academic Emergency Medicine, 2017)
Warfarin induced skin necrosis (WISN) is a rare but important side effect of warfarin. Early diagnosis may lessen the amount of permanent tissue damage and can prevent progression to full thickness skin necrosis. So, physicians should be aware of such a complication. Screening for protein C or S or anti-thrombin deficiencies, or presence of anti-phospholipid antibodies before beginning warfarin therapy, could be helpful to avoid high levels of international normalized ratio (INR). Here, we report a 54-year-old man who presented to the emergency department with acral and penile gangrene following prolonged use of warfarin.